Gastric, pancreatic, and biliary responses to meals in hyperthyroidism. Issue 8 (August 1980) - Miller, L J; Owyang, C; Malagelada, J R; Gorman, C A; Go, V L
Abstract : Upper gastrointestinal function in response to a mixed nutrient meal was evaluated in hyperthyroid patients, both before and after therapy, and in healthy controls. Gastric secretion, gastric emptying, and pancreatic secretion were all normal and normally integrated postprandially in the hyperthyroid patients. Bile acid output was reduced (P less than 0.05) in this group of patients relative to healthy controls. Duodenal bile acid concentrations, however, were above the critical micellar concentration in most of the hyperthyroid patients, and the bile acid output and concentration remained unchanged in all patients three months after treatment. After radioactive iodine therapy, when gastrointestinal symptoms were returning toward normal, a small but statistically significant increase in gastric secretion was observed. However, gastric emptying and pancreatic secretion, like biliary secretion, remained unchanged. Abnormalities responsible for the diarrhoea and steatorrhoea in hyperthyroidism appear to reside primarily distal to the duodenum. However, reduced bile acid output may be a contributory factor in some patients.